In Vitro Evaluation of Antioxidant, Anticancer, and Anti-Inflammatory Activities of Ethanolic Leaf Extract of Adenium obesum - Alshehri, Ahmad; Ahmad, Afza; Tiwari, Rohit Kumar; Ahmad, Irfan; Alkhathami, Ali G.; Alshahrani, Mohammad Y.; Asiri, Mohammed A.; Almeleebia, Tahani M.; Saeed, Mohd; Yadav, Dharmendra Kumar; Ansari, Irfan Ahmad (Frontiers in Pharmacology, 2022)
Adenium obesum is commonly known as ‘desert rose’ belongs to family apopcynaceae has previously been reported for its anti-influenza, antimicrobial, cytotoxic efficacies and well-known for their ethno medicinal applications. In the present study, ethanolic extracts of A. obesum (AOE) were analyzed gas chromatography-mass spectrometry (GC–MS) to identify the important phytochemical componuds. The GC–MS analysis of AOE detected the presence of 26 phytochemical compounds. This plant is traditionally used for the treatment of various diseases. In this report, the antioxidant, anti-inflammatory and anticancer activities of ethanolic leaf extract from A. obesum (AOE) were studied. The antioxidative potential of ethanolic extract of AOE was examined by different antioxidant assays, such as antioxidant capacity by the DPPH, ABTS, superoxide, hydroxyl radicals scavenging and lipid peroxidation inhibition assays. The antioxidant activities of various reaction mixtures of AOE were compared with reference or standard antioxidants (ascorbic acid). In addition, we also evaluated the anticancer activity of AOE and it was observed that AOE was found to be cytotoxic against A549 lung cancer cells. It was found AOE inhibited the viability of A549 lung cancer cells by inducing nuclear condensation and fragmentation. Furthermore, ethanolic AOE demonstrated anti-inflammatory potential of AOE in murine alveolar macrophages (J774A.1) as an in vitro model system. AOE showed its potential in reducing the levels of inflammatory mediators include the proinflammatory cytokines and TNF-α. The results obtained in the present investigation established the antioxidative, anticancer and anti-inflammatory potency of AOE, which may account for subsequent studies in the formulation of herbal-based medicine.